Bahaya Erosi dan Upaya Konservasi Padang Pengembalaan Sapi di Aceh Besar - Romi Rinaldi; Hairul Basri; Manfarizah Manfarizah (Jurnal Manajemen Sumberdaya Lahan, 2012)
Erosion Hazard Rate and Conservation Effort of Rifle Range at Aceh Besar Abstract: The objectives of the study were to predict levels of erosion hazard and to determine appropriate conservation efforts at pasture of Superior Livestock Breeding Centers (SLBC) of Aceh Cow in Indrapuri, Aceh Besar District. The study used a descriptive survey method. Erosion hazard rate (EHR) was analyzed using USLE formula. Result showed that potential erosion hazard rates in the pasture of the SLBC for each map units of land (MUL) from the largest to the smallest were MUL 2 (456,35 ton ha-1 year-1), MUL 6 (351,52 ton ha-1 year-1), MUL 1 (208,96 ton ha-1 year-1), MUL 3 (160,47 ton ha-1 year-1), MUL 4 (66,63 ton ha-1 year-1), and MUL 5 (6,52 ton ha-1 year-1). There were three classifications of potential EHR, i.e. heavy in MUL 1, 2 and 6; medium in MUL 3 and 4; and very lighting MUL 5. Actual EHR from the biggest to the smallest were MUL 6 (175,76 ton ha-1 year-1), MUL 2 (132,34 ton ha-1 year-1), MUL 1 (60,60 ton ha-1 year-1), MUL 5 (3,26 ton ha-1 year-1), MUL 3 (3,21 ton ha-1 tahun-1), and MUL 4 (1,33 ton ha-1 tahun-1). There were two actual HER i.e. medium in MUL 1, 2 and 6 and very lighting MUL 3, 4, and 5. Direction of appropriate land use in the pasture of SLBC of Aceh Cow in Indrapuri was to apply a vegetative conservation method by planting and propagating urinam grass (Brachiaria decumbens), bladygrass (Imperatacy lindrica) and elephant grass (Pennisetum purpureum).Abstrak: Penelitian ini bertujuan untuk memprediksi tingkat bahaya erosi yang terjadi  dan menentukan upaya konservasi yang tepat pada padang penggembalaan di Balai Pembibitan Ternak Unggul (BPTU) Sapi Aceh Kecamatan Indrapuri Aceh Besar. Metode yang digunakan adalah metode survey. Analisis Tingkat Bahaya Erosi (TBE) dihitung dengan menggunakan rumus USLE. Tingkat Bahaya Erosi potensial yang terjadi pada padang penggembalaan di BPTU Sapi Aceh Indrapuri berkisar antara 456,35- 6,52 ton ha-1 th-1. Terdapat tiga klasifikasi TBE potensial yaitu berat, sedang,dan  sangat ringan . Sedangkan Tingkat Bahaya Erosi aktual adalah 175,76-1,33 ton ha-1 th-1. Terdapat dua klasifikasi TBE aktual yaitu sedang dan sangat ringan. Arahan penggunaan lahan yang tepat pada padang penggembalaan di BPTU Sapi Aceh Indrapuri adalah menerapkan tindakan konservasi metode vegetatif dengan cara menanam dan memperbanyak rumput Brachiaria decumbens, rumput alang-alang (Imperata cylindrica) dan rumput gajah (Pennisetum purpureum).